Determination of Volatile Compounds of Mentha piperita and Lavandula multifida and Investigation of Their Antibacterial, Antioxidant, and Antidiabetic Properties. (14th June 2022) - Hamad Al-Mijalli, Samiah; ELsharkawy, Eman R.; Abdallah, Emad M.; Hamed, Munerah; El Omari, Nasreddine; Mahmud, Shafi; Alshahrani, Mohammed Merae; Mrabti, Hanae Naceiri; Bouyahya, Abdelhakim
Abstract : Mentha piperita and Lavandula multifida are widely used in Moroccan traditional medicine for the treatment of diabetes and infectious diseases. The aims of this work were the determination of the chemical composition of Mentha piperita (MPEO) and Lavandula multifida (LMEO) essential oils and the evaluation of their antibacterial, antioxidant, and antidiabetic activities. The chemical composition was determined by GC-MS analysis. The antibacterial effects were evaluated against several bacterial strains using disc diffusion, MIC, and MBC methods. The antioxidant activity was evaluated in vitro using DPPH, H2 O2, and xanthine oxidase, and the antidiabetic activity was estimated by the inhibitory effects of α -amylase, α -glucosidase, and lipase activities. GC-MS results showed that the main compounds of MPEO were menthone (29.24%), levomenthol (38.73%), and eucalyptol (6.75%). However, eucalyptol (28.11%), 2-bornanone (11.57%), endo-borneol (7.82%), and linalyl acetate (5.22%) are the major compounds of LMEO. The results exhibited important inhibitory effects against some bacterial strains with MIC = MBC = 0.39 mg/mL for MPEO against Staphylococcus aureus ATCC. However, LMEO exhibited remarkable antioxidant and antidiabetic activities compared to MPEO. Indeed, LMEO inhibited DPPH, H2 O2, and xanthine oxidase with concentrations of 15.23, 21.52, and 8.89  µ g/mL, respectively. Moreover, LMEO exhibited α -amylase and α -glucosidase at IC50  = 85.34 and IC50  = 59.36  µ g/mL, respectively. The findings showed that both MPEO and LMEO exhibit promising biological properties. However, the application of these species or their main bioactive compounds requires further investigation.